1995
DOI: 10.1099/00221287-141-1-123
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase B from Serratia marcescens BJL200 is exported to the periplasm without processing

Abstract: A gene encoding a chitinase from Serratia marcescens BJLZOO was cloned and expressed in Escherichia coli and S. marcescens. Nucleotide sequencing revealed an open reading frame encoding a 555 kDa protein of 499 amino acids without a typical signal peptide for export. The cellular localization of the chitinase was studied, using two types of cell fractionation methods and immunocytochemical techniques. These analyses showed that the chitinase is located in the cytoplasm in E. coli, whereas it is exported to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 44 publications
1
61
0
Order By: Relevance
“…We synthesized the azide-bearing inhibitor 3 as a reactive scaffold for capturing complementary acetylenic reagents to form triazole-linked inhibitors by TGS. Competition assay with 4-methylumberiferyl diacetylchitobiose (4-MU-(GluNAc) 2 ) 34,35 showed that this azide-bearing inhibitor 3 expressed a low inhibitory activity similar to that of the azide-lacking inhibitor 2, which are in striking contrast to the potency of the natural product 1. Hence, amide derivatives of azide 3 with amines other than methylamine were made and tested to see whether the binding could be restored to a level that would make azide 3 a sufficiently good anchor at the active site, to be used for the capture of alkyne-bearing candidates through in situ triazole formation.…”
Section: Resultsmentioning
confidence: 49%
“…We synthesized the azide-bearing inhibitor 3 as a reactive scaffold for capturing complementary acetylenic reagents to form triazole-linked inhibitors by TGS. Competition assay with 4-methylumberiferyl diacetylchitobiose (4-MU-(GluNAc) 2 ) 34,35 showed that this azide-bearing inhibitor 3 expressed a low inhibitory activity similar to that of the azide-lacking inhibitor 2, which are in striking contrast to the potency of the natural product 1. Hence, amide derivatives of azide 3 with amines other than methylamine were made and tested to see whether the binding could be restored to a level that would make azide 3 a sufficiently good anchor at the active site, to be used for the capture of alkyne-bearing candidates through in situ triazole formation.…”
Section: Resultsmentioning
confidence: 49%
“…For construction of a gene encoding His 10 -ChiB-E144Q (i.e. a variant of ChiB that is inactive due to mutation of the catalytic acid [16]), the pET16b-His 10 -ChiB construct and a pMAY2-10 variant encoding ChiB-E144Q were digested with BamHI. Cleavage of the latter plasmid resulted in a fragment of approximately 820 bp containing part of the chiB gene carrying the E144Q mutation, which was then ligated with the 5090 bp BamHI fragment derived from the cleaved pET16b-His 10 -ChiB construct.…”
Section: Construction Of His 10 -Chib-e144qmentioning
confidence: 99%
“…It showed pesticidal effects against a number of plant pathogens including Rhizoctonia solani and Fusarium oxysporium causing wilt disease [6]. Serratia marcescens, a gram negative bacterium, soil inhabitant, is very efficient in degradation of chitin because of its ability to produce different chitinolytic enzymes [7]. Chitinase production and its activity depends on a number of limiting factors viz., culture state, temperature and pH of media etc.…”
Section: Introductionmentioning
confidence: 99%